2019
DOI: 10.1001/jamadermatol.2018.5360
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ProspectiveHLA-B*13:01Screening to Prevent Dapsone Hypersensitivity Syndrome in Patients With Leprosy

Abstract: ; and the Dapsone Hypersensitivity Syndrome Prevention Working Group IMPORTANCE Dapsone hypersensitivity syndrome (DHS) is the most serious adverse reaction associated with dapsone administration and one of the major causes of death in patients with leprosy, whose standard treatment includes multidrug therapy (MDT) with dapsone, rifampicin, and clofazimine. Although the HLA-B*13:01 polymorphism has been identified as the genetic determinant of DHS in the Chinese population, no studies to date have been done to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 35 publications
1
41
0
Order By: Relevance
“…The results have been independently validated in various Asian populations including Thais[ 15 ], Koreans[ 16 ], Indians[ 17 ] and Taiwanese[ 18 ]. Screening for this allele in new leprosy patients before the initiation of MDT has proven beneficial to reduce incidence rate of DHS in China to zero[ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results have been independently validated in various Asian populations including Thais[ 15 ], Koreans[ 16 ], Indians[ 17 ] and Taiwanese[ 18 ]. Screening for this allele in new leprosy patients before the initiation of MDT has proven beneficial to reduce incidence rate of DHS in China to zero[ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, DPS‐specific cytotoxic T cells were significantly activated when cocultured with HLA‐B*13:01 ‐expressing antigen‐presenting cells in the presence of DPS . A prospective study demonstrated that HLA‐B*13:01 screening and DPS elimination from multidrug therapy for treating leprosy for patients harboring the HLA‐B*13:01 allele was an effective strategy for reducing the incidence of DIHS in the Chinese population …”
Section: Resultsmentioning
confidence: 99%
“…The frequency of this allele in southern Chinese (10.47%) is higher than that in northern Chinese (5.85%), which might be the reason for high TIHS incidence found in southern China, especially in Guangdong Province. Across the world, HLA-B*13:01 is rare in Caucasian and African, but has a higher frequency in Asian population 23. The association between HLA-B*13:01 and TIHS has been observed in Japanese 7.…”
Section: Discussionmentioning
confidence: 99%